2022
DOI: 10.4102/phcfm.v14i1.3428
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing trans women in men who have sex with men populations and their health access in East Africa: A Tanzanian study

Abstract: We will use the current terminology, trans woman, to refer to a person who identifies as a woman and whose sex assigned at birth was male, based on the World Health Organization's (WHO) definition: '[t]ransgender is an umbrella term that describes a diverse group of people Background: Few data are available on the presence and characteristics of transgender populations in sub-Saharan Africa (SSA), which makes the provision of health services for key populations difficult.Aim: This study aimed to ascertain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In seven of the included studies, participants indicated that financial constraints deterred them from accessing desired services, such as PrEP and GAC [ 27 , 35 , 38 , 44 , 46 , 47 , 50 ]. The inability to afford medications, treatment, medical bills, and transportation to and from healthcare facilities limited participants’ access to care [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In seven of the included studies, participants indicated that financial constraints deterred them from accessing desired services, such as PrEP and GAC [ 27 , 35 , 38 , 44 , 46 , 47 , 50 ]. The inability to afford medications, treatment, medical bills, and transportation to and from healthcare facilities limited participants’ access to care [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inability to afford medications, treatment, medical bills, and transportation to and from healthcare facilities limited participants’ access to care [ 27 ]. Two studies highlighted how the lack of insurance coverage for various healthcare services, including GAC, prevented service access [ 38 , 47 ]. One study reported that the most common reason individuals chose not to take PrEP was a lack of medical insurance coverage [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are limited data in Kenya and sub-Saharan Africa on processes of gender development and gender-related sense of self, gender perception, gender expression, gender presentation, and gender identity and labels; such assessment would inform gender-affirming interventions [ 41 ]. Among 300 MSM participants in a Tanzanian study, 17% identified as “transsexual or transgender”, and among those, 70% identified themselves as a “woman” [ 42 ]. This study further identified that time spent “living as a woman” was variable among participants identifying as transsexual or transgender, and authors acknowledged that varying concepts of the transfeminine identity may have led to misclassification.…”
Section: Discussionmentioning
confidence: 99%